Theory and Education in the Limits of the Capital - Maria Ciavatta (Universidade Federal do Rio Grande do Sul, 2022)
In this article we deal with theory and education and the different contexts in which the limits of capital, its historicity and relations with human life are located. Another aspect of our reflection is education in the sense of human formation. First, we deal with the historicity of historical materialism; secondly, we present some fundamental concepts for educational research; third, we bring the history of the present and its relationship with authoritarianism in Brazil; finally, we point out the social limits of the capital system its contradictions and the recognition of the dialectical space of the phenomena that establish counter-hegemonic forms of thought and action.